2018
DOI: 10.1186/s12931-018-0767-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the healthcare resource use associated with inappropriate prescribing of inhaled corticosteroids for people with chronic obstructive pulmonary disease (COPD) in GOLD groups A or B: an observational study using the Clinical Practice Research Datalink (CPRD)

Abstract: BackgroundRecent recommendations from the Global Initiative for Chronic Obstructive Lung Disease (GOLD) position inhaled corticosteroids (ICS) for use in chronic obstructive pulmonary disease (COPD) patients experiencing exacerbations (≥ 2 or ≥ 1 requiring hospitalisation); i.e. GOLD groups C and D. However, it is known that ICS is frequently prescribed for patients with less severe COPD. Potential drivers of inappropriate ICS use may be historical clinical guidance or a belief among physicians that intervenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 26 publications
2
26
1
Order By: Relevance
“…Previous studies have also demonstrated similar issues in this setting, largely regarding the overprescription of ICS/LAMA/LABA triple therapy [19]. Inappropriate ICS prescription as described here and in previous studies exposes patients to unnecessary safety issues like pneumonia [20], and also increases the healthcare resource use associated with treatment [21].…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies have also demonstrated similar issues in this setting, largely regarding the overprescription of ICS/LAMA/LABA triple therapy [19]. Inappropriate ICS prescription as described here and in previous studies exposes patients to unnecessary safety issues like pneumonia [20], and also increases the healthcare resource use associated with treatment [21].…”
Section: Discussionsupporting
confidence: 53%
“…31 In a population-based study in the UK, ICS was inappropriately prescribed in almost half of GOLD A/B patients with COPD. 6 Moreover, in this study, addition of ICS did not provide additional clinical benefit.…”
Section: Use Of Ics In Copdcontrasting
confidence: 46%
“…10,18 Moreover, management of COPD by appropriate nonpharmacologic interventions, such as smoking cessation, nutritional counseling, vaccination, and pulmonary rehabilitation, should also be considered ( Figure 2). Although use of ICS is recommended in high-risk patients or GOLD group D, 10,19 ICS are frequently inappropriately prescribed outside current treatment recommendations for patients with less severe COPD as well, 6,8 which is both not of value and potentially dangerous due to adverse effects.…”
Section: Global Initiative For Chronic Obstructive Lung Disease Patiementioning
confidence: 99%
See 1 more Smart Citation
“…Real-life observational data from a UK primary care database of GOLD A or B patients have also shown no differences in health resource use comparing open triple therapy vs LABA/LAMA. 10 The DACCORD real-life observational study from Germany looked at 377 infrequently exacerbating patients mostly GOLD B, who were switched to IND/GLY having previously been taking open triple therapy. 11 Over the 1 year of follow-up after switching, there was no increase in exacerbations while 52% had a clinically relevant improvement in COPD Assessment Test score.…”
Section: Introductionmentioning
confidence: 99%